Phosphorus-friendly transgenics. Transgenic animals engineered to express a bacterial enzyme that liberates phosphate from animal feed may provide a solution to a common form of environmental pollution - Ward, KA (Nature biotechnology, 2001)
Environmental pollution attributable to intensive animal agriculture is increasingly recognized as a serious ecological problem. In this issue, transgenic mice have been engineered to more efficiently metabolize phosphates from feed, thereby reducing the phosphate content of their excreta. Once adapted to large animals, this approach could lower the phosphate content of manure from intensively reared livestock and potentially reduce the risk of phosphate contamination of water sources. Inorganic phosphate is frequently added to animal feed to facilitate optimal growth. This is because phytate (inositol hexaphosphoric acid), a naturally occurring phosphate present in cereal grains, legumes, and oilseeds, etc., is resistant to absorption by animals. When excess phosphate leached from manure enters our waterways, it can stimulate algal blooms and eutrophication. Thus, the livestock industry is actively seeking ways of ensuring that the effluent from intensively reared animals contains less phosphate than at present. One potential solution is to supplement animal feed with phosphorolytic enzymes that promote release of the mineral from plant material. The addition of phytase, a bacterial enzyme that releases phytate from animal feed, can eliminate the need for dietary phosphorus supplementation. But this approach is costly and the enzyme is subject to partial or complete inactivation during preparation and storage of the feed. Golovan et al. have taken a more direct approach by genetically manipulating phosphate metabolism in the animal itself. In their paper, they describe how a bacterial gene encoding phytase, inserted into the mouse genome by transgenic techniques and modified for expression in the animal's salivary glands, can significantly reduce the amount of phosphate excreted by a transgenic mouse compared with nontransgenic controls. Bacterial phytase is secreted by the salivary glands of the transgenic mice, thus providing a stable and cost-free source of the enzyme. Golovan et al. report an 11% reduction in the fecal phosphorus content of their transgenic mice and suggest that this figure will be substantially higher in animals such as pigs, because mice probably recycle fecal phytate through coprophagy.